Plan de negocio para la creación de una hacienda turística en la parroquia el Chaupi, cantón Mejía - Yánez Ortiz, Carlos Rafael (2019)
This final paper is based on the creation of a business plan for a tourist farm located in Parroquia El Chaupi-Cantón Mejía, having as specific objectives the development of strategic planning, marketing strategies, an operational plan and the financial evaluation. A methodology was established focused on the research of a mixed approach. This means qualitative and quantitative methods, throughout these methods there can be more information about the visitors. With strategic planning, the company was based on quality processes and services focused on the client. This will analyze internal and external elements of the organization. For the marketing chapter this product will be sold through social networks, digital platforms, and the push promotion. The operative plan details how to be an entrepreneur and all the necessary equipment for its functioning. Finally, the financial plan revealed that the projects feasible since the margin of result is positive with the 31%.